Quantum incompatibility from the viewpoint of entanglement theory - Heinosaari T (United Kingdom, 2022)
In this essay I discuss certain analogies between quantum incompatibility and entanglement. It is an expanded version of my talk presented at Mathematical Foundations of Quantum Mechanics in memoriam Paul Busch, held in York in June 2019.
Mathematical Foundations of Quantum Mechanics - in memoriam Paul Busch 18th - 19th June 2019, York, United Kingdom